Bioassays Guided Fractionation of Senna occidentalis for Identification of Natural Antifungal Constituents Against Macrophomina phaseolina - JAVAID,A. (2017)
ABSTRACT Macrophomina phaseolina is one of the most destructive soil-borne fungal plant pathogens. In the present study, different aerial parts of Senna occidentalis were analyzed for their antifungal activity against M. phaseolina. In initial screening bioassays, 0.5-3.0% concentrations of methanolic extracts of fruit, leaf and stem were tested against M. phaseolina. The methanolic leaf extract showed the greatest activity causing up to 29% suppression in biomass production of M. phaseolina. Fractionation of leaf extract of S. occidentalis was carried out with four organic solvents. Bioassays with a range of concentrations (2.34-150 mg mL-1) of these sub-fractions revealed that the chloroform sub-fraction was the most effective, causing 93-98% reduction in the biomass of M. phaseolina, followed by 59-92% suppression in fungal biomass due to the n-hexane sub-fraction. The ethyl acetate and n-butanol sub-fractions were only effective at higher concentrations. GC-MS analysis of chloroform sub-fraction was performed to identify different compounds. Six compounds were identified in this fraction; 1,3-benzenedicarboxylic acid, bis(2-ethylhexyl) ester was the predominant compound (53.55%) followed by 9,10-dimethyltricyclo[4.2.1.1 (2,5)]decane-9,10-diol (22.68%), cyclohexanol, and 2-(2-hydroxy-2-propyl)-5-methyl (9.87%).